2009
DOI: 10.1038/aps.2009.166
|View full text |Cite|
|
Sign up to set email alerts
|

The combination of baicalin and baicalein enhances apoptosis via the ERK/p38 MAPK pathway in human breast cancer cells

Abstract: Aim:To examine whether the cell growth inhibitory effect of the combination of baicalin and baicalein is related to apoptosis. Moreover, to determine whether the expression of some apoptosis-related proteins is regulated by the ERK/p38 MAPK pathway. Methods: Cell viability was measured using a 3-(4,5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay. Apoptosis was detected by acridine orange (AO) staining, DNA ladder assay and flow cytometric analysis. Apoptosis-related proteins were observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
65
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(65 citation statements)
references
References 43 publications
0
65
0
Order By: Relevance
“…Similarly, baicalein has been reported to have an inhibitory effect on ERK1/2 phosphorylation in both in vivo and in vitro (Agarwal et al, 2009;Gao et al, 2013;Chen et al, 2013;Liang et al, 2012;Zhou et al, 2013). On the other hand opposite effects have also been reported for baicalein, baicalin and galangin, suggesting cellor tissue-specific effects (Chen et al, 2006;Lei et al, 2012;Liu et al, 2013;Zhou et al, 2009). These data together with the recent findings of the research group of Dr. Masahiko Negishi defining the indirect activation of CAR via EGFR inhibition (Mutoh et al, 2013) urge for a comprehensive study of the molecular mechanism of their interactions with CAR.…”
Section: Discussionmentioning
confidence: 87%
“…Similarly, baicalein has been reported to have an inhibitory effect on ERK1/2 phosphorylation in both in vivo and in vitro (Agarwal et al, 2009;Gao et al, 2013;Chen et al, 2013;Liang et al, 2012;Zhou et al, 2013). On the other hand opposite effects have also been reported for baicalein, baicalin and galangin, suggesting cellor tissue-specific effects (Chen et al, 2006;Lei et al, 2012;Liu et al, 2013;Zhou et al, 2009). These data together with the recent findings of the research group of Dr. Masahiko Negishi defining the indirect activation of CAR via EGFR inhibition (Mutoh et al, 2013) urge for a comprehensive study of the molecular mechanism of their interactions with CAR.…”
Section: Discussionmentioning
confidence: 87%
“…p38 is usually activated by inflammatory cytokines and leads to cell apoptosis [16,18] . Interestingly, several recent papers revealed different data about the activation of ERK or p38 in the CD151 signaling path way [6,7,26] .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, a "transmembrane linker" model for CD151 has been proposed, and CD151 signaling is thought to be mediated by CD151-integrin complexes [6,14,15] . Mitogen-activated protein (MAP) kinases play important roles in various cellular responses [16][17][18] . In this study, using a gene transfer technique with a recombinant adeno-associated virus (rAAV) vector, we examined the roles of MAP kinases, particularly extracellular signal-regulated kinase (ERK) and p38 MAP kinase (p38), in CD151-induced endothelial cell proliferation, migration and tube formation.…”
Section: Introductionmentioning
confidence: 99%
“…Liquiritin confers neuroprotective effects against focal cerebral ischemia/reperfusion in mice via its antioxidant and antiapoptosis properties (Sun et al, 2010). Baicalin and baicalein confer anticancer properties via the ERK/p38 MAPK pathway in human breast cancer cells (Zhou et al, 2009). The anti-inflammatory effects of ferulic acid (Huang et al, 2011) and glycyrrhizin (Kudo et al, 2011) were also reported.…”
Section: Introductionmentioning
confidence: 94%